2015
DOI: 10.1016/j.procir.2015.08.048
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Turning of AL6063 under Cryogenic Pre Cooled Condition

Abstract: One of the major issues faced while machining Aluminium and its alloys is built up edge and hence reduced tool life and surface finish. Turning temperature and friction have to be reduced to avoid sticking and built up edges. This work deals turning of AL 6063 rod at two environments a) Pre cooling to sub zero temperature using dry ice and b) Dry turning at room temperature. Depth of cut is kept constant at 2.5mm. Turning inserts CNMG 120408 MP TT 5100 and CCGT 120408 FC K10 -1 were used. Cutting speeds of 70,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Applying CO 2 flow in liquid form is another technique of cryogenic cooling. Murugappan et al [111] implemented precooling cryogenic using dry ice and two different types cutting inserts in turning Al 6063. The experimental results showed that insert type and cooling techniques have influential effect on productivity and product quality.…”
Section: Cryogenic Cooling With Dry Ice or Co 2 Snowmentioning
confidence: 99%
“…Applying CO 2 flow in liquid form is another technique of cryogenic cooling. Murugappan et al [111] implemented precooling cryogenic using dry ice and two different types cutting inserts in turning Al 6063. The experimental results showed that insert type and cooling techniques have influential effect on productivity and product quality.…”
Section: Cryogenic Cooling With Dry Ice or Co 2 Snowmentioning
confidence: 99%
“…Therefore, different studies investigated the effects of the input variables (cutting speed v c , feed rate f, depth of cut a p , tool-tip radius r ε , etc.) on surface roughness [13][14][15][16]. The surface roughness is commonly associated with f (mm/rev.)…”
Section: Introductionmentioning
confidence: 99%